The Hedging Ability of Gold, Silver and Bitcoin against Inflation in ASEAN Countries - Shaista Arshad; Thi Hong Nhung Vu; Too Shaw Warn; Loke Mei Ying (Asian Academy of Management Journal of Accounting and Finance, 2023)
This paper examines the hedging ability of gold, silver, and Bitcoin against inflation in ASEAN countries. The inclusion of Bitcoin as a hedge is relatively new in literature and the effect of hedging has been exacerbated post Global Financial Crisis, when the prices of precious metals have increased continuously. To serve that objective, the student-t EGARCH (1,1) model is first used to study the relationship between average asset return and inflation and next a quantile regression model is applied to explore the relationship between different quantiles of asset return and inflation. This ensures the hedging potential of each asset to be equally strong in bearish and bullish conditions. The tests show that the results from student-t EGARCH (1,1) model and quantile regression model are different while the results pre and post GFC are similar in most of the cases. The quantile regression model, which accounts for different quantiles for asset returns, indicates that gold, silver, and Bitcoin appear to be a hedge and safe haven in ASEAN countries. However, from the student-t EGARCH (1,1) model, which accounts for average asset returns, Bitcoin is a hedge asset but none of the three assets serves as a safe haven in ASEAN countries.